Developing RME-based lesson study for learning community in the learning environment of high school mathematics teachers - Rusiyanti, Rini Herlina; Zulkardi; Putri, Ratu Ilma Indra; Somakim (Journal on Mathematics Education, 2022)
Teachers' academic and professional competencies significantly improve the quality of their learning. An ongoing process is needed to support and develop their quality. This study developed a learning environment through the Realistic Mathematics Education (RME)-based Lesson Study for Learning Community (LSLC) for high school mathematics teachers. The model is valid and practical and potentially affects the learning quality of high school mathematics teachers. The research employed a design research method of development studies was conducted in three stages: the preliminary stage, the development or prototyping stage, and the assessment stage. Prototyping development is a formative evaluation in which the phases include self-evaluation, expert review, one-to-one, small group, and field tests. The research subjects were 15 high school mathematics teachers from four schools in Palembang. Data was collected through questionnaires, observation, and documentation. The research has resulted in a valid and practical teachers’ working group-learning community-class model that potentially affects high school, mathematics teachers. The learning environment is in the form of training in working groups for mathematics teachers, teacher mentoring in learning communities in schools, and teacher assessment learning processes in the classroom. The learning tools were produced using the RME-based LSLC system. The data analysis shows that the learning environment using the RME-based LSLC model can make high school mathematics teachers significantly understand learning, design learning tools, carry out learning, and evaluate learning. Consequently, the teachers’ academic competence and professionalism significantly improve their learning.